Stabilizing a Multimachine Power System via Output Feedback Excitation Control - ., Hardiansyah (Faculty of Engineering, Universitas Tanjungpura, 2010)
Abstract This paper presents a modified optimal controller for stabilizing a multimachine power system. The design method does not need the specification of weighting matrices. The eigenvalues of electromechanical modes would be shifted to a pre-specified vertical strip. For practical implementation, the proposed method design using an optimal reduced order model whose state variables are torque angles and speeds. The reduced order model retains their physical meaning and is used to design output feedback controller that takes into account the realities and constraints of the electrical power systems. Effectiveness of this controller is evaluated and example, a multimachine power system is given to illustrate the advantages and effectiveness of the proposed approach. Keywords dynamic stability, strip eigenvalue assignment, power system stabilizer, optimal reduced-order model, output feedback excitation control